THE USE OF SOCIAL MEDIA TO PROMOTE BUSINESSES - David Giménez Britez, Fernando; Sebastian Meza Montiel , Giovani; Mathias Báez, Richard; Vicente González, Matias; Martin Lopez González, Bruno (Revista Gênero e Interdisciplinaridade, 2023)
At present, social networks such as Facebook, Instagram and Twitter have an important role in promoting business. This work focuses on exploring why social media is important to promote a business effectively and how it can benefit businesses in the digital world. The focus of the research is quantitative, since surveys are applied and the results are tabulated in Excel and then represented in percentage statistical graphs. It is important to note that this work has certain limitations. Since the field of social media evolves rapidly, it’s possible that some findings are based on information that can quickly become outdated. The technique for data collection used in this work will be the survey, it will be composed of closed questions that are related to the objectives in order to clarify the tasks to be investigated. As a result, it is concluded that social media plays a crucial role in driving business success today. These platforms offer a number of benefits, such as the ability to reach a global audience, build direct relationships with customers, and promote brand growth. By following a solid strategy and generating relevant, quality content, businesses can take full advantage of the potential of social media to increase their brand visibility, improve customer loyalty, and increase sales.